Optimal unemployment insurance design: Time limits, monitoring, or workfare - Peter Fredriksson; Bertil Holmlund (Institute for Labour Market Policy Evaluation (IFAU), 2005)
This paper analyses crucial design features of unemployment insurance (UI) policies. We examine three different means of improving the efficiency of UI: the duration of benefit payments, monitoring in conjunction with sanctions, and workfare. To that end we develop a quantitative model of equilibrium unemployment. The model features worker heterogeneity in preferences for leisure. The numerical analysis suggests that a system with monitoring and sanctions restores search incentives most effectively, since it brings additional incentives to search actively so as to avoid the sanction. Therefore, the UI provider can offer a more generous UI replacement rate in a system with monitoring and sanctions than in the other two systems. Workfare appears to be inferior to the other two systems.
Keywords: J64; J68; 330; Unemployment insurance; search equilibrium; time limits; monitoring and sanctions; workfare; Arbeitslosenversicherung; Aktivierende Sozialhilfe; Arbeitsuche; Ökonomischer Anreiz; Schweden